2012
DOI: 10.1097/iop.0b013e31825e6a88
|View full text |Cite
|
Sign up to set email alerts
|

The Causative Factors or Characteristics of the Asian Double Eyelid

Abstract: The thickness of orbicularis oculi muscle or its bending shape, and the thickness of the skin at the skin crease, are major causative factors in Asian double eyelid formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…7 In conclusion, our in vivo study in young healthy volunteers confirms previous published anatomical differences between single and double eyelids in cadavers. 9 The single eyelid shows slightly thicker SOOC both in the pretarsal area and at the eyelid crease but not at 5 mm above the eyelid crease level.…”
Section: Discussionmentioning
confidence: 98%
“…7 In conclusion, our in vivo study in young healthy volunteers confirms previous published anatomical differences between single and double eyelids in cadavers. 9 The single eyelid shows slightly thicker SOOC both in the pretarsal area and at the eyelid crease but not at 5 mm above the eyelid crease level.…”
Section: Discussionmentioning
confidence: 98%
“…Hirohiko et al and Yulan et al verified that the preseptal orbicularis muscle was the anatomical etiologic factor of the epicanthus in their anatomical examination. 11,12 Hirohiko et al found that the preseptal orbicularis fasciculi ran obliquely around the epicanthus and coincided with the direction of the epicanthus in their anatomical study. They also reasoned that the epicanthus formation depended on the intermuscular fibers of the oblique direction of the preseptal orbicularis muscle.…”
Section: Evolution Of the Epicanthus (Kwon's Theory): Etiology And Prmentioning
confidence: 92%
“…56 Kakizaki and associates 56 performed an experimental anatomical study to address this issue and found that the thickness of orbicularis oculi muscle or the way it folds (bending shape) and the thickness of the skin at the skin crease are major causative factors in Asian double-eyelid formation. It has evolved over the years to yield consistent results.…”
Section: Blepharoplastymentioning
confidence: 99%